STUDI TENTANG PERAN CAMAT DALAM UPAYA MENINGKATKAN PELAYANAN E-KTP DI KANTOR KECAMATAN KENOHAN KABUPATEN KUTAI KARTANEGARA - Sugiarto .; Nur Fitriyah; Adam Idris (Jurnal Administrative Reform, 2017)
This research aims to know the role of the head of sub-district  in improving the e-ID cards in Kenohan Sub-district Office Kutai Kartanegara Regency. This research also wants to know the factor that supporting and the factors that restricting the role of the head of sub-district  in improving the e-ID cards in Kenohan Sub-district Office Kutai Kartanegara Regency. This research uses qualitative research methods type descriptive. Analysis tool used is an interactive model of the analysis as presented by Miles and Huberman.